Diseño sonoro ambisonics para una narrativa audiovisual en video 360 integrado a un ambiente de realidad virtual (2019)
The technological development in the audiovisual field has introduced 360 videos as an alternative to generate immersive experiences such as those achieved by videogames and virtual reality, and it has created the need to integrate sound environments that accompany and support the experience, tools such as Ambisonics sound with the B-Format have been standardized for the creation of sound environments. This work aims to achieve a sound design for a 360 video using Ambisonics for Unity, creating a virtual reality environment, not before generating a methodology that specifies a logical procedure that facilitates its realization, besides comparing 2 tools for the production of Ambisonics audio, highlighting its pros and cons. It was possible to propose a functional methodology that includes processes of preproduction, production and postproduction, which trace the path to achieve an immersive sound design that complements the experience generated by a 360 video, tools such as Facebook Spatial Workstation were used on the DAW Reaper for the creation of the B-Format and Logic X for the creation of the original music.